Correlation of cord Blood pH with Nucleated RBC and Serum LDH in Neonates with Perinatal Asphyxia - S B, Chiranth; Avabratha, K. Shreedhara (Journal of Nepal Paediatric Society, 2022)
Introduction: Perinatal asphyxia is one of the leading causes of neonatal mortality in developing countries. No single indicator has good diagnostic efficacy for perinatal asphyxia and only a combination of various indices may help in diagnosis. This study aims at determining the utility of serum lactate dehydrogenase (LDH) and cord blood nucleated red blood cell (nRBC) count as surrogate markers to pH in perinatal asphyxia. Methods: It is an observational study done over a period of 18 months. All newborn babies fitting into inclusion criteria were enrolled into the study. After initial resuscitation, cord blood was sent for pH and nRBC analysis and serum LDH levels was estimated from first collected blood sample (within six hours). Data was collected on excel sheet, Pearson’s correlation coefficients and ROC curves were used to tabulate results. Results: Our study included 74 neonates with perinatal asphyxia. Mean pH was 6.99 (SD - 0.138). Mean nRBC count was 38 / 100 WBC (SD17.9) and mean LDH level was 1478 IU / L (SD - 429). Cord blood pH showed significant (p < 0.001) correlation with raising nRBC count and LDH levels ROC plot showed nRBC count (AUC: 0.7866) and Serum LDH (AUC: 0.8143) as very good predictors of severe acidosis in perinatal asphyxia. Conclusions: Cord blood nRBC count and serum LDH levels are significantly increased in perinatal asphyxia and correlate well with severity of acidosis. Nucleated RBC count and serum LDH can be used as surrogate markers to diagnose perinatal asphyxia.